Effects of exercise with music in frail older adults: a systematic review and meta-analysis - NamHee Kim; Gwang Suk Kim; Min Kyung Park; Layoung Kim; Jae Jun Lee; Seungbum Yang (BMJ Open)
Objectives Frail older adults need to improve their health through exercise, and effective interventions are necessary to ensure their participation. Exercise with music has been shown to enhance adherence among older adults and improve both physical and mental health outcomes, making it a suitable intervention for frail older adults. This study evaluated the impact of exercise with music on the physical and emotional health of frail, community-dwelling older adults.Design A systematic review and meta-analysis were conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines.Data sources MEDLINE, Cumulative Index to Nursing and Allied Health Literature, Embase, Cochrane Library, PsycINFO, Google Scholar and the Virginia Henderson International Nursing Library were last searched on 14 March 2025.Eligibility criteria for selecting studies We included randomised controlled trials (RCTs) and non-RCTs that applied exercise with music to community-dwelling frail older adults.Data extraction and synthesis Five independent reviewers used standardised methods to search, screen and code included studies. Study quality was assessed using the revised Cochrane Risk of Bias 2 tool and the Risk of Bias in Non-Randomized Studies of Interventions tool. A meta-analysis and narrative synthesis were conducted, and the findings were summarised using Grading of Recommendation, Assessment, Development, and Evaluation evidence profiles. Publication bias was checked, and sensitivity analyses were used to assess the robustness of the results.Results After screening the initial 1425 studies, 17 studies (13 RCTs and 4 non-RCTs) were analysed. The overall risk of bias indicated that two had high risk and three had serious risk among the RCTs, and two had serious risk and two had moderate risk among the non-RCTs included in the meta-analysis. As for physical health outcomes, studies reported on frailty, Timed Up and Go (TUG), handgrip strength, falls, balance, gait speed, endurance and other performance. As for emotional health outcomes, studies reported on depression, social support and activities, quality of life or satisfaction and cognitive function. The pooled analysis suggested that exercise with music may have a positive effect on reducing frailty (standardised mean difference (SMD)=−0.20, 95% CI=−0.34 to −0.07, p=0.003, I2=0%; very low certainty) and decreasing depression levels (SMD=−0.40, 95% CI=−0.65 to −0.15, p=0.002, I2=0%; very low certainty) compared with control group outcomes in non-RCTs. However, there was no effect on the TUG and handgrip strength. A narrative synthesis of evidence suggested potential beneficial effects on frailty and depression.Conclusions Exercise with music may help improve frail older adults’ physical and emotional health and potentially reduce the burden of frailty. However, further rigorous investigation is needed, as the evidence has a very low level of certainty. Additionally, results from this review should be interpreted with caution because of concerns associated with the risk of bias. Community-based health professionals should consider using music when providing exercise interventions to frail older adults, while applying tailored approaches that consider their unique needs.PROSPERO registration number CRD42022369774.